Exploring food culture in India: Negotiating access, uses and experiences among migrant students using social media - Srinivasa, Sapna Mysore; Karuthamakkakath, Muhammed Swalih (Communications in Humanities and Social Sciences, 2024)
Migration, short term or long term is a shift from a certain set of norms and practices to another one. This is a change which happens gradually. Among migrants, food culture can stay intact, or there can be a mixture of home and host food culture, or they can completely change to the culture of the host place. Social media’s role in cultural communication and food communication has been investigated largely by academicians.  The current study investigates the role of social media in the food habits and the shift in culinary culture among interstate migrant students. One part of the study deals with how students cope with the new culinary environment which is different from their original one with the help of social media. The second part deals with the hands of social media in the exploration of the new food culture. The study occupies a questionnaire survey among interstate migrant students from Kerala who are studying across India to understand about the questions.